Optimized short-forms of the Cognitive Distortions Questionnaire. (December 2022) - Morrison, Amanda S.; Ustun, Berk; Horenstein, Arielle; Kaplan, Simona C.; de Oliveira, Irismar Reis; Batmaz, Sedat; Gross, James J.; Sadikova, Ekaterina; Hemanny, Curt; Pires, Pedro P.; Goldin, Philippe R.; Kessler, Ronald C.; et al.
Abstract: Introduction: The Cognitive Distortions Questionnaire (CD-Quest) is a self-report questionnaire that assesses common cognitive distortions. Although the CD-Quest has excellent psychometric properties, its length may limit its use. Methods: We attempted to develop short-forms of the CD-Quest using RiskSLIM – a machine learning method to build short-form scales that can be scored by hand. Each short-form was fit to maximize concordance with the total CD-Quest score for a specified number of items based on an objective function, in this case R 2, by selecting an optimal subset of items and an optimal set of small integer weights. The models were trained in a sample of US undergraduate students ( N = 906). We then validated each short-form on five independent samples: two samples of undergraduate students in Brazil ( N s = 182, 183); patients with depression in Brazil ( N = 62); patients with social anxiety disorder in the US ( N = 198); and psychiatric outpatients in Turkey ( N = 269). Results: A 9-item short-form with integer scoring was created that reproduced the total 15-item CD-Quest score in all validation samples with excellent accuracy (R 2 = 90.4-93.6%). A 5-item ultra-short-form had good accuracy (R 2 = 78.2-85.5%). Discussion: A 9-item short-form and a 5-item ultra-short-form of the CD-Quest both reproduced full CD-Quest scores with excellent to good accuracy. These shorter versions of the full CD-Quest could facilitate measurement of cognitive distortions for users with limited time and resources. Highlights: The Cognitive Distortions Questionnaire (CD-Quest) assesses 15 common distortions. Machine-learning optimized short-forms of the CD-Quest were developed. CD-Quest data sources were six independent clinical and nonclinical samples. Integer weights allow hand-scoring to reproduce total CD-Quest scores. 9- and 5-item short forms reproduced total scores with excellent to good accuracy.